Study on the two points-pasted reinforcement corrosion monitoring method based on FBG - Sun, L.; Zhu, C.; Chen, C.; Li, Jun (2017)
Reinforcement corrosion speed monitoring is the precondition of durability evaluation of concrete structures, reliability calculation, residual lifetime prediction and engineering structural reinforcement. Electrolyte electricity accelerated reinforcement corrosion tests have been designed to simulate the actual engineering conditions of reinforcement corrosion process. A method named two points-pasted reinforcement corrosion monitoring has been advanced in this paper. The relationship between wavelength change value and reinforcement corrosion rate has been put up so that reinforcement corrosion condition can be estimated indirectly. The further development of the early reinforcement corrosion online monitoring technology has been done. It has vital significance to find problems and prevent damage through the reinforced concrete structure health diagnosis.